Coated active material, electrode material, and battery

By using a fluoride solid electrolyte coating and fine structure with high content of Ti-O-F bonds in the battery, the problem of increased resistance in the battery's durability test is solved, and the durability and charge and discharge efficiency of the battery are improved.

CN119301770APending Publication Date: 2025-01-10PANASONIC HOLDINGS CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380044362.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-10
Filing Date
2023-05-09
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The problem of the increase in resistance of existing batteries in durability tests is that, especially when using solid electrolytes with poor oxidation resistance, it is difficult to effectively suppress the increase in resistance.

Method used

Using fluoride containing Ti as the coating layer of solid electrolyte, ensure that the total ratio of Ti-O-F bond and Ti-O bond is greater than 70%, and the coating layer is optimized through the fine particle structure and pore structure to improve the coating active substances and other materials. engagement and interface performance.

Benefits of technology

It effectively suppresses the increase in battery resistance, improves the durability and charge and discharge efficiency of the battery, especially when using halide solid electrolyte with excellent oxidation resistance, it significantly improves the ion conductivity and battery performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301770A_ABST
    Figure CN119301770A_ABST
Patent Text Reader

Abstract

This coated active material (130) is provided with an active material (110) and a coating layer (111) that contains a first solid electrolyte and covers at least a part of the surface of the active material (110), the first solid electrolyte containing a Ti-containing fluoride, and the ratio of the total of Ti-O-F bonds and Ti-O bonds in a bond group to Ti contained in the first solid electrolyte being greater than 70%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a coated active material, an electrode material, and a battery. Background Art

[0002] Non-Patent Document 1 discloses a battery using a sulfide as a solid electrolyte.

[0003] Prior art literature

[0004] Non-patent literature

[0005] Non-patent document 1: Journal of Power Sources 159 (2006), p193-199. Summary of the invention

[0006] Problems to be solved by the invention

[0007] In the prior art, it is necessary to suppress the increase in battery resistance caused by a durability test.

[0008] Means used to solve problems

[0009] The present disclosure provides a coated active material, which comprises:

[0010] Active substances, and

[0011] a coating layer comprising a first solid electrolyte and covering at least a portion of the surface of the active material,

[0012] The first solid electrolyte includes a fluoride containing Ti,

[0013] The ratio of the total of Ti—OF bonds and Ti—O bonds in the bond group to Ti contained in the first solid electrolyte is greater than 70%.

[0014] Effects of the Invention

[0015] According to the present disclosure, it is possible to suppress an increase in battery resistance caused by a durability test. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a cross-sectional view showing a schematic structure of the coated active material according to the first embodiment.

[0017] Figure 2 It is a cross-sectional view showing a schematic structure of a coated active material according to a modified example.

[0018] Figure 3 This is a cross-sectional view showing a schematic structure of an electrode material according to the second embodiment.

[0019] Figure 4This is a cross-sectional view showing a schematic structure of a battery according to Embodiment 3.

[0020] Figure 5A This is a graph showing the Ti2p XPS spectrum of the coated active material of Example 1.

[0021] Figure 5B This is a graph showing the Ti2p XPS spectrum of the coated active material of Comparative Example 1.

[0022] Figure 6 This is a graph showing the relationship between the Ti bonding ratio and the increase rate of the resistance. DETAILED DESCRIPTION

[0023] (Understanding that forms the basis of the present disclosure)

[0024] For example, when the active material is in contact with the solid electrolyte, the solid electrolyte may be oxidatively decomposed during battery charging. This tendency is more pronounced when the solid electrolyte has poor oxidation resistance, such as sulfide solid electrolytes. In order to solve this problem, the surface of the active material is coated with a coating material with excellent oxidation resistance, such as a halide solid electrolyte.

[0025] Here, the present inventors noticed that even if the composition of the coating material is the same, there will be differences in battery characteristics, especially resistance. Furthermore, the present inventors found that there is a correlation between the bonding state of Ti contained in the coating layer covering the active material and the battery characteristics, and conceived the present disclosure.

[0026] (Overview of one aspect of the present disclosure)

[0027] The coated active material according to the first aspect of the present disclosure includes:

[0028] Active substances, and

[0029] a coating layer comprising a first solid electrolyte and covering at least a portion of the surface of the active material,

[0030] The first solid electrolyte includes a fluoride containing Ti,

[0031] The ratio of the total of Ti—OF bonds and Ti—O bonds in the bond group to Ti contained in the first solid electrolyte is greater than 70%.

[0032] According to the present disclosure, it is possible to suppress an increase in battery resistance caused by a durability test.

[0033] In the second aspect of the present disclosure, for example, in the coated active material according to the first aspect, the above ratio may be 92% or less. According to such a configuration, the bonding property between the coated active material and other materials is improved.

[0034] In the third aspect of the present disclosure, for example, for the coated active material according to the first or second aspect, the aforementioned coating layer may have a granular structure including a plurality of particles with a diameter of 500 nm or less. If the coating layer has a fine granular structure, the deformation of the coating layer is promoted during the manufacture of the electrode plate, and thus a good interface can be formed between the coated active material and other materials. As a result, the resistance of the battery can be further reduced.

[0035] In the fourth aspect of the present disclosure, for example, for the coated active material according to any one of the first to third aspects, the aforementioned coating layer may have a plurality of pores with a diameter of 50 nm or less. If the coating layer has fine pores, the deformation of the coating layer is promoted during the manufacture of the electrode plate, and thus a good interface can be formed between the coated active material and other materials. As a result, the resistance of the battery can be further reduced.

[0036] In the fifth aspect of the present disclosure, for example, for the coated active material according to any one of the first to fourth aspects, the mass of the aforementioned coating layer may be 4.5% or less of the mass of the aforementioned coated active material. According to this configuration, the resistance of the battery can be further reduced.

[0037] In the sixth aspect of the present disclosure, for example, for the coated active material according to any one of the first to third aspects, the aforementioned active material may be a positive electrode active material. If the technology of the present disclosure is applied to the positive electrode active material, a solid electrolyte with poor antioxidant properties but high ionic conductivity can be used for the positive electrode.

[0038] In the seventh aspect of the present disclosure, for example, for the coated active material according to any one of the first to sixth aspects, the aforementioned first solid electrolyte may be represented by the following compositional formula (2). Here, x satisfies 0 < x ≤ 1.2, n is the weighted average valence of the elements contained in M, M is a metal or a semi-metal and contains at least Ti, and X contains fluorine or contains fluorine and chlorine. When the halide solid electrolyte represented by the compositional formula (2) is used in the battery, the charge and discharge efficiency of the battery can be improved.

[0039] Li 6-nx M x X6… Formula (2)

[0040] In the eighth aspect of the present disclosure, for example, for the coated active material according to the seventh aspect, M may be at least one selected from the group consisting of Ca, Mg, Al, Y, Ti, and Zr. Among them, M contains Ti. According to this configuration, the ionic conductivity of the coating layer can be improved, and the resistance of the battery can be effectively reduced.

[0041] In the ninth aspect of the present disclosure, for example, in the coated active material according to the seventh aspect, M may be at least one selected from the group consisting of Al, Ti and Zr. M includes Ti. According to this configuration, the ion conductivity of the coating layer can be improved, and the resistance of the battery can be effectively reduced.

[0042] In the tenth aspect of the present disclosure, for example, in the coated active material according to the seventh aspect, M may be Ti or may be Ti and Al. In this case, the halide solid electrolyte exhibits high ion conductivity.

[0043] In the eleventh aspect of the present disclosure, for example, in the coated active material according to the seventh aspect, the ratio of the amount of Li to the total amount of M can be 1.7 to 4.2. With this configuration, the ion conductivity of the first solid electrolyte can be further improved.

[0044] The electrode material according to the twelfth aspect of the present disclosure includes:

[0045] Any one of the first to eleventh aspects of the invention, and

[0046] Second solid electrolyte.

[0047] In a thirteenth aspect of the present disclosure, for example, in the electrode material according to the twelfth aspect, the second solid electrolyte may include a sulfide solid electrolyte.

[0048] A battery according to a fourteenth aspect of the present disclosure includes:

[0049] A positive electrode comprising the electrode material according to the twelfth or thirteenth aspect.

[0050] A battery according to a fifteenth aspect of the present disclosure includes:

[0051] A positive electrode comprising the electrode material of the twelfth or thirteenth aspect,

[0052] Negative electrode, and

[0053] An electrolyte layer is disposed between the positive electrode and the negative electrode.

[0054] The electrode material disclosed herein is suitable for suppressing an increase in battery resistance caused by a durability test.

[0055] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments.

[0056] (Implementation Method 1)

[0057] Figure 11 is a cross-sectional view showing a schematic structure of the coated active material 130 according to Embodiment 1. The coated active material 130 includes an active material 110 and a coating layer 111. The active material 110 is in the shape of particles, for example. The coating layer 111 covers at least a portion of the surface of the active material 110.

[0058] The coating layer 111 is a layer containing a first solid electrolyte. The coating layer 111 is provided on the surface of the active material 110. The first solid electrolyte contains a fluoride. The fluoride contains Ti.

[0059] The first solid electrolyte may be a solid electrolyte containing a halogen. A solid electrolyte containing a halogen is often also referred to as a halide solid electrolyte. The halide solid electrolyte has excellent oxidation resistance. In particular, a halide solid electrolyte containing fluorine (F) has excellent oxidation resistance due to its high electronegativity. Therefore, by coating the active material 110 with the first solid electrolyte, oxidation of other solid electrolytes in contact with the active material 110 can be suppressed. Thus, the increase in battery resistance caused by the endurance test can be suppressed.

[0060] In the present embodiment, the total ratio of Ti-O bonds and Ti-OF bonds in the bond group to Ti contained in the first solid electrolyte is greater than 70%. That is, the ratio of Ti atoms bonded to oxygen atoms is high. The high ratio of Ti bonded to oxygen indicates that the coating layer 111 forms a good interface with the active material 110. In the stage before forming the coating layer 111, most of the Ti atoms contained in the first solid electrolyte exist in the form of Ti atoms forming Ti-F bonds. In the coating process for forming the coating layer 111, the first solid electrolyte is attached to the surface of the active material 110 by pressing the first solid electrolyte on the surface of the active material 110. In addition, the Ti contained in the first solid electrolyte is bonded to the oxygen on the surface of the active material 110, and the Ti-O bonds and Ti-OF bonds are increased. The coating layer 111 is chemically bonded to the active material 110, so that the coating layer 111 can follow the expansion and contraction of the active material 110 during charging and discharging. Therefore, the increase in battery resistance caused by the endurance test can be suppressed by the coated active material 130 having a high total ratio of Ti-O bonds and Ti-OF bonds. The total ratio of Ti-O bonds and Ti-OF bonds may be 77% or more, or 82% or more.

[0061] The total ratio of Ti-O bonds and Ti-OF bonds in the bond group of Ti can be 92% or less. In this case, there are particles of the coating material that are not completely bonded to the active material 110. Such particles make it possible to deform the coating layer 111 in the densification process when manufacturing the electrode plate, thereby improving the bonding between the coated active material 130 and other materials.

[0062] The bond group to Ti represents a group of anionic bonds to Ti. Titanium (Ti), fluorine (F) and oxygen (O) typically form compounds of TiF4, TiOF2 and TiO2. Therefore, the bond group to Ti is represented by Ti-F bonds, Ti-OF bonds and Ti-O bonds. By appropriately adjusting the total ratio of Ti-O bonds and Ti-OF bonds in these bond groups, the first solid electrolyte contained in the coating layer 111 can be given excellent bonding properties.

[0063] The ratio of Ti-O bonds and Ti-OF bonds can be determined by the following method. First, XPS (X-ray Photoelectron Spectroscopy) measurement of the coated active material 130 is performed. The spectrum of Ti2p appearing in the range of binding energy (Binding Energy) of 448eV to 486eV is separated into peaks of TiF4, TiOF2 and TiO2. The ratio of the sum of the area of ​​the peak belonging to the Ti-O bond and the area of ​​the peak belonging to the Ti-OF bond to the total area of ​​the separated peaks is calculated as the ratio of Ti-O bonds and Ti-OF bonds in the bond group of Ti (unit: %).

[0064] In this embodiment, the active material 110 may be an oxide. The active material 110 may be an oxide that does not contain Ti.

[0065] The resistance of the battery increases after a predetermined endurance test. The ratio of the resistance after the endurance test to the resistance before the endurance test is the resistance increase factor (%).

[0066] The increase in resistance caused by the endurance test can be measured by the following method. After the battery is completed, the charge and discharge process is performed. Then, the battery is charged to an appropriate charging voltage of about 2V to 4V. Then, it is discharged at an appropriate rate of about 2C to 4C. The resistance (initial resistance) is calculated by dividing the difference between the open circuit voltage just before discharge and the voltage at the moment 10 seconds after the start of discharge by the discharge current value. The resistance obtained is the resistance before the endurance test. Then, the battery is placed in a high temperature tank set to 60°C, and 90 cycles of charge and discharge are repeated at 1C. Then, the battery is returned to the constant temperature tank at 25°C, and the resistance is measured as described above. The resistance obtained is the resistance after the endurance test.

[0067] The coating layer 111 can uniformly coat the active material 110 .

[0068] The coating layer 111 may cover only a portion of the surface of the active material 110. Since the particles of the active material 110 are in direct contact with each other via the portion not coated by the coating layer 111, the electron conductivity between the particles of the active material 110 is improved. As a result, the battery can operate at a high output power.

[0069] A portion of the coating layer 111 may have a granular structure comprising a plurality of particles having a diameter of 500 nm or less. Particles having a diameter of 500 nm or less are particles of a halide solid electrolyte serving as a coating material. If the coating layer 111 has a fine granular structure, deformation of the coating layer 111 is promoted during manufacture of the electrode plate, thereby enabling a good interface to be formed between the coated active material 130 and other materials. As a result, the resistance of the battery can be further reduced. When the particles are too large, deformation of the solid electrolyte serving as the coating material is required, so it is difficult to obtain the effects described above. The lower limit of the particle diameter is not particularly limited, and is, for example, 5 nm.

[0070] The granular structure refers to a structure in which a plurality of particles having a diameter of 500 nm or less are strung together and arranged irregularly. The diameter of each of the plurality of particles constituting the granular structure may be 50 nm or less.

[0071] The granular structure including a plurality of particles having a diameter of 500 nm or less can be formed by using particles having a sufficiently small diameter as the coating material and appropriately adjusting the energy applied by a processing device when forming the coating layer 111 .

[0072] The coating layer 111 may have a plurality of pores with a diameter of 50 nm or less. If the coating layer 111 has fine pores, deformation of the coating layer 111 is promoted when manufacturing the electrode plate, so that a good interface can be formed between the coated active material 130 and other materials. As a result, the resistance of the battery can be further reduced. The diameter of each of the plurality of pores may be 5 nm or less. The lower limit of the diameter of the pore is not particularly limited, for example, 0.5 nm.

[0073] Pores having a diameter of 50 nm or less can be formed by using particles having a sufficiently small diameter as the coating material and appropriately adjusting the energy applied by a processing device when forming the coating layer 111 .

[0074] The “plurality of particles having a diameter of 500 nm or less” and the “plurality of pores having a diameter of 50 nm or less” can be identified by observing the surface of the coated active material 130 at a magnification of, for example, 100,000 times using a scanning electron microscope.

[0075] The mass of the coating layer 111 may be 4.5% or less of the mass of the coated active material 130. If the mass of the coating layer 111 is 4.5% or less of the mass of the coated active material 130, the resistance of the battery can be further reduced. The lower limit of the mass of the coating layer 111 is not particularly limited, and is, for example, 0.1% of the mass of the coated active material 130.

[0076] Next, the active material 110 and the coating layer 111 will be described in detail.

[0077] Active Substance 110

[0078] The active material 110 is, for example, a positive electrode active material. If the technology disclosed in the present invention is applied to the positive electrode active material, a solid electrolyte having poor oxidation resistance but high ion conductivity can be used for the positive electrode. Examples of such solid electrolytes include sulfide solid electrolytes, halide solid electrolytes, and the like.

[0079] The positive electrode active material includes a material having the characteristics of absorbing and releasing metal ions (such as lithium ions). As the positive electrode active material, lithium-containing transition metal oxides, transition metal fluorides, polyanion materials, fluorinated polyanion materials, transition metal sulfides, transition metal oxysulfides, transition metal oxynitrides, etc. can be used. In particular, when lithium-containing transition metal oxides are used as the positive electrode active material, the manufacturing cost of the battery can be reduced and the average discharge voltage can be increased. As lithium-containing transition metal oxides, Li(NiCoAl)O2, Li(NiCoMn)O2, LiCoO2, etc. can be listed.

[0080] The positive electrode active material may include Ni, Co and Al. The positive electrode active material may be lithium nickel cobalt aluminum oxide. For example, the positive electrode active material may be Li(NiCoAl)O2. According to this structure, the energy density and charge and discharge efficiency of the battery can be further improved.

[0081] The active material 110 has a particle shape, for example. The shape of the particles of the active material 110 is not particularly limited. The shape of the particles of the active material 110 may be spherical, ellipsoidal, scaly, or fibrous.

[0082] The median particle size of the active material 110 may be greater than 0.1 μm and less than 100 μm. When the median particle size of the active material 110 is greater than 0.1 μm, the coated active material 130 and other solid electrolytes can form a good dispersion state. As a result, the charge and discharge characteristics of the battery are improved. When the median particle size of the active material 110 is less than 100 μm, the diffusion rate of lithium inside the active material 110 can be fully ensured. Therefore, the battery can operate at a high output power.

[0083] In this specification, the “median diameter” refers to the particle diameter at which the cumulative volume in the volume-based particle size distribution is 50%. The volume-based particle size distribution is measured, for example, by a laser diffraction measuring device or an image analyzer.

[0084] 《Coating layer 111》

[0085] The coating layer 111 contains a first solid electrolyte. The first solid electrolyte has ion conductivity. The ion conductivity is typically lithium ion conductivity. The coating layer 111 may contain the first solid electrolyte as a main component, or may contain only the first solid electrolyte. "Main component" refers to the component that contains the most by mass ratio. "Containing only the first solid electrolyte" means that no materials other than the first solid electrolyte are actively added except for inevitable impurities. For example, inevitable impurities include raw materials for making the first solid electrolyte, by-products generated when the first solid electrolyte is produced, etc. The ratio of the mass of inevitable impurities to the overall mass of the first coating layer 111 can be less than 5%, less than 3%, less than 1%, or less than 0.5%.

[0086] The median particle size of the particles of the coating material used to form the coating layer 111 can be 500 nm or less. When the median particle size of the particles of the coating material is 500 nm or less, the particles of the coating material can be uniformly diffused on the surface of the active material 110. Furthermore, mechanical energy is applied to the particles of the active material 110 and the coating material to eliminate the voids contained therein, thereby forming a thin and uniform coating layer 111. The median particle size of the particles of the coating material can be 100 nm or less, or it can be 60 nm or less. The lower limit of the median particle size of the particles of the coating material is not particularly limited, for example, it is 1 nm.

[0087] The particles of the coating material used to form the coating layer 111 may be particles of the first solid electrolyte.

[0088] In this specification, "particles" may be aggregates of particles or particles composed of a single particle. That is, particles may be secondary particles or primary particles.

[0089] The specific surface area of ​​the particles of the coating material used to form the coating layer 111 may be 10 m 2 / g or more, can also be 20m 2 / g or more, can also be 40m 2 / g or more. A large specific surface area of ​​the coating material particles is associated with a large volume of the coating material. When the specific surface area of ​​the coating material particles is large, the surface of the active material 110 can be uniformly coated. As a result, a uniform coating layer 111 can be formed. The upper limit of the specific surface area of ​​the coating material particles is not particularly limited, and is, for example, 100m 2 / g.

[0090] The first solid electrolyte is a solid electrolyte containing fluorine. The first solid electrolyte may contain Li, M, and X. X contains F and may also contain at least one selected from the group consisting of Cl, Br, and I. M may be at least one selected from the group consisting of Ca, Mg, Al, Y, Ti, and Zr. The ionic conductivity and antioxidant property of this material are excellent. Therefore, the coated active material 130 having the coated layer 111 of the first solid electrolyte can improve the charge-discharge efficiency and thermal stability of the battery.

[0091] When X is F, the antioxidant property of the first solid electrolyte can be further improved.

[0092] The halide solid electrolyte as the first solid electrolyte is represented by the following compositional formula (1), for example. In compositional formula (1), α, β, and δ are each independently a value greater than 0. X contains fluorine.

[0093] Li α M β X δ … Formula (1)

[0094] Compared with halide solid electrolytes such as LiI formed only by Li and halogen elements, the halide solid electrolyte represented by compositional formula (1) has a higher ionic conductivity. Therefore, when the halide solid electrolyte having the composition represented by compositional formula (1) is used in a battery, the charge-discharge efficiency of the battery can be improved.

[0095] The halide solid electrolyte as the first solid electrolyte can be represented by the following compositional formula (2). x satisfies 0 < x ≤ 1.2. n is the weighted average valence of the elements contained in M. M is a metal or semi-metal and contains Ti. X contains fluorine or contains fluorine and chlorine. When the halide solid electrolyte represented by compositional formula (2) is used in a battery, the charge-discharge efficiency of the battery can be improved.

[0096] Li 6-nx M x X6… Formula (2)

[0097] M may be at least one selected from the group consisting of Ca, Mg, Al, Y, Ti, and Zr. Among them, M contains Ti. By introducing polyvalent ions into the crystal structure containing Li and F, the conduction path of lithium ions can be expanded. According to this structure, the ionic conductivity of the coated layer 111 can be improved, and the resistance of the battery can be effectively reduced.

[0098] M can be at least one selected from the group consisting of Al, Ti, and Zr. Among them, M contains Ti. By adding the above elements as trivalent or tetravalent polyvalent ions to the crystal structure containing Li and F, the conduction path of lithium ions can be expanded. According to this configuration, the ionic conductivity of the coating layer 111 can be improved, and the resistance of the battery can be effectively reduced.

[0099] M can be Ti. Alternatively, M can also be Ti and Al. In this case, the halide solid electrolyte exhibits high ionic conductivity.

[0100] In order to further improve the ionic conductivity of the first solid electrolyte, in the halide solid electrolyte, the ratio of the amount of substance of Li to the total amount of the amount of substance of M can be 1.7 or more and 4.2 or less. According to this configuration, the ionic conductivity of the first solid electrolyte can be further improved.

[0101] The halide solid electrolyte can be substantially formed of Li, Ti, Al, and X. Here, "the halide solid electrolyte is substantially formed of Li, Ti, Al, and X" means that the molar ratio (i.e., mole fraction) of the total amount of the amount of substance of Li, Ti, Al, and X to the total amount of the amount of substance of all elements constituting the halide solid electrolyte is 90% or more. As an example, this molar ratio (i.e., mole fraction) can be 95% or more. The halide solid electrolyte can be formed only of Li, Ti, Al, and X.

[0102] The halide solid electrolyte can be represented by the following compositional formula (3).

[0103] Li 6-(4-x)b (Ti 1-x M x ) b F6… Formula (3)

[0104] In the compositional formula (3), 0 < x < 1 and 0 < b ≤ 1.5 are satisfied. The halide solid electrolyte having this composition has high ionic conductivity.

[0105] In order to further improve the ionic conductivity of the halide solid electrolyte, in the compositional formula (3), M can be Al.

[0106] In order to further improve the ionic conductivity of the halide solid electrolyte, in the compositional formula (3), 0.1 ≤ x ≤ 0.9 can be satisfied.

[0107] In the compositional formula (3), 0.1 ≤ x ≤ 0.7 can be satisfied.

[0108] The upper limit and lower limit of the range of x in composition formula (3) can be specified by any combination of numerical values ​​selected from 0.1, 0.3, 0.4, 0.5, 0.6, 0.67, 0.7, 0.8 and 0.9.

[0109] In order to improve the ion conductivity of the halide solid electrolyte, in the composition formula (3), 0.8≤b≤1.2 may be satisfied.

[0110] The upper limit and lower limit of the range of b in composition formula (3) can be specified by any combination of numerical values ​​selected from 0.8, 0.9, 0.94, 1.0, 1.06, 1.1 and 1.2.

[0111] The halide solid electrolyte may be crystalline or amorphous.

[0112] The shape of the halide solid electrolyte is not particularly limited. The shape of the halide solid electrolyte is, for example, needle-shaped, spherical, or ellipsoidal. The shape of the halide solid electrolyte may be granular.

[0113] When the shape of the halide solid electrolyte is, for example, a particle shape (eg, a spherical shape), the halide solid electrolyte may have a median particle size of 0.01 μm or more and 100 μm or less.

[0114] The thickness of the coating layer 111 is, for example, greater than 1 nm and less than 500 nm. If the thickness of the coating layer 111 is appropriately adjusted, the contact between the active material 110 and other solid electrolytes can be sufficiently suppressed. The thickness of the coating layer 111 can be determined by thinning the coated active material 130 by ion milling or the like and observing the cross section of the coated active material 130 with a transmission electron microscope. The average value of the thickness measured at any multiple positions (e.g., 5 points) can be regarded as the thickness of the coating layer 111.

[0115] The halide solid electrolyte may be a sulfur-free solid electrolyte. In this case, the generation of sulfur-containing gases such as hydrogen sulfide gas from the solid electrolyte can be avoided. A sulfur-free solid electrolyte refers to a solid electrolyte represented by a composition formula that does not contain sulfur elements. Therefore, a solid electrolyte containing a very small amount of sulfur, such as a solid electrolyte having a sulfur content ratio of 0.1% by mass or less, belongs to a sulfur-free solid electrolyte. The halide solid electrolyte may also contain oxygen as an anion other than the halogen element.

[0116] 《Method for producing halide solid electrolyte》

[0117] The halide solid electrolyte can be produced by the following method.

[0118] A plurality of raw material powders corresponding to the target composition are prepared and mixed. The raw material powder may be a halide. The halide may be a compound formed of a plurality of elements including a halogen element.

[0119] For example, when the target composition is Li 2.7 Ti 0.3 Al 0.7 In the case of F6, LiF, TiF4 and AlF3 are prepared as raw material powders at a molar ratio of about 2.7:0.3:0.7 and mixed. At this time, by appropriately selecting the type of raw material powder, the element type of "M" and "X" in the composition formula (1) can be determined. By adjusting the type of raw material powder, the mixing ratio of the raw material powder and the synthesis process, the values ​​of "α", "β", "γ" and "δ" in the composition formula (1) can be adjusted. In order to offset the composition changes that may occur in the synthesis process, the raw material powders can be mixed at a pre-adjusted molar ratio.

[0120] The raw material powders can be mixed using a mixing device such as a planetary ball mill. The raw material powders are reacted with each other by a mechanochemical grinding method to obtain a reactant. The reactant can be calcined in a vacuum or in an inert atmosphere. Alternatively, the mixture of the raw material powders can be calcined in a vacuum or in an inert atmosphere to obtain a reactant. The calcination is performed, for example, at a temperature of 100° C. to 400° C. for more than 1 hour. In order to suppress composition changes that may occur during calcination, the raw material powders can be calcined in a closed container such as a quartz tube. After these steps, a halide solid electrolyte can be obtained.

[0121] 《Method for producing coated active material 130》

[0122] The coated active material 130 can be produced by the following method.

[0123] The powder of the active material 110 and the powder of the first solid electrolyte are mixed in an appropriate ratio to obtain a mixture. The mixture is subjected to a grinding process to impart mechanical energy to the mixture. The grinding process may be performed using a mixing device such as a ball mill. In order to suppress oxidation of the material, the grinding process may be performed in a dry atmosphere and an inactive atmosphere.

[0124] The coated active material 130 can be manufactured by a dry particle composite method. The treatment based on the dry particle composite method includes applying at least one mechanical energy selected from the group consisting of impact, compression and shear to the active material 110 and the first solid electrolyte. The active material 110 and the first solid electrolyte are mixed in an appropriate ratio.

[0125] The device used in the manufacture of the coated active material 130 is not particularly limited, and may be a device capable of imparting mechanical energy of impact, compression or shear to the mixture of the active material 110 and the first solid electrolyte. As devices capable of imparting mechanical energy, there can be cited processing devices (particle composite devices) such as a ball mill, "MECHANO FUSION" (manufactured by Hosokawa Micron Corporation), "Nobilta" (manufactured by Hosokawa Micron Corporation), and "BALANCE GRAN" (manufactured by FREUND-TURBOCorporation).

[0126] "MECHANO FUSION" is a particle compounding device that uses dry mechanical compounding technology based on applying strong mechanical energy to a variety of different raw material powders. In MECHANO FUSION, mechanical energy such as compression, shearing and friction is applied to the raw material powders placed between a rotating container and a press head. This causes the particles to be compounded.

[0127] "Nobilta" is a particle compounding device that uses dry mechanical compounding technology developed from particle compounding technology to compound nanoparticles. Nobilta produces composite particles by applying mechanical energy such as impact, compression, and shear to various raw material powders.

[0128] The "Nobilta" rotates a rotor at high speed in a horizontal cylindrical mixing container with a predetermined gap between the rotor and the inner wall of the mixing container, and repeatedly forces the raw material powder to pass through the gap. In this way, impact, compression and shear forces act on the mixture, and composite particles of the active material 110 and the first solid electrolyte can be produced.

[0129] The "BALANCE GRAN" stirs the powder in a spiral shape from the outer circumference to the inner circumference, has a chopper to promote convection, and has a stirring scraper that rotates in the opposite direction to the chopper. Through these actions, the mixture can be evenly dispersed to produce composite particles.

[0130] In any device, the thickness of the coating layer 111 and the specific surface area of ​​the coated active material 130 can be controlled by adjusting the rotation speed, processing time, dosage, particle size of the material, etc. As the processing time increases, the specific surface area decreases. As the rotation speed of the device increases, the specific surface area decreases.

[0131] If the rotation speed of the device is increased, the mechanical energy given to the particles increases, and the Ti-O bonds and Ti-OF bonds increase. Increasing the treatment time is also effective for increasing the Ti-O bonds and Ti-OF bonds. By adjusting the rotation speed of the device, the treatment time, etc. according to the median particle size of the active material 110 and the median particle size of the first solid electrolyte, a coated active material 130 having a desired ratio of Ti-O bonds and Ti-OF bonds can be obtained. For example, as the amount of the first solid electrolyte as the coating material increases, the Ti-F bond tends to increase.

[0132] It should be noted that the treatment based on the above-mentioned device is not essential. The coated active material 130 can be manufactured by mixing the active material 110 with the first solid electrolyte using a mortar, a mixer, etc. The first solid electrolyte can be deposited on the surface of the active material 110 by various methods such as spraying, spray dry coating, electrodeposition, impregnation, and mechanical mixing using a disperser.

[0133] (Variation Example)

[0134] Figure 2 1 is a cross-sectional view showing a schematic structure of a coated active material 140 of a modified example. The coated active material 140 includes an active material 110 and a coating layer 120. In this modified example, the coating layer 120 includes a first coating layer 111 and a second coating layer 112. The first coating layer 111 is a layer including a first solid electrolyte. The second coating layer 112 is a layer including a base material. The first coating layer 111 is located outside the second coating layer 112. According to this structure, the resistance of the battery can be further reduced.

[0135] The first covering layer 111 is the covering layer 111 described in the first embodiment.

[0136] The second covering layer 112 is located between the first covering layer 111 and the active material 110. In this modification, the second covering layer 112 is in direct contact with the active material 110. The second covering layer 112 may include a material having low electron conductivity, such as an oxide material or an oxide solid electrolyte, as a base material.

[0137] In the present modification as well, the total ratio of the Ti—OF bond and the Ti—O bond in the bond group to Ti is larger than 70%.

[0138] Examples of oxide materials include SiO2, Al2O3, TiO2, B2O3, Nb2O5, WO3, and ZrO2. Examples of oxide solid electrolytes include Li-Nb-O compounds such as LiNbO3, Li-BO compounds such as LiBO2 and Li3BO3, Li-Al-O compounds such as LiAlO2, Li-Si-O compounds such as Li4SiO4, Li2SO4, and Li4Ti5O12 Li-Ti-O compounds such as Li2ZrO3, Li-Zr-O compounds such as Li2MoO3, Li-VO compounds such as LiV2O5, Li-WO compounds such as Li2WO4, etc. The base material may be one selected from these or a mixture of two or more.

[0139] The base material may be a solid electrolyte having lithium ion conductivity. The base material is typically an oxide solid electrolyte having lithium ion conductivity. The oxide solid electrolyte has high ion conductivity and excellent high potential stability. By using an oxide solid electrolyte as a base material, the charge and discharge efficiency of the battery can be improved.

[0140] The base material may be a material containing Nb. The base material typically contains lithium niobate (LiNbO3). According to this structure, the charge and discharge efficiency of the battery can be improved. For the oxide solid electrolyte as the base material, the material described above can also be used.

[0141] In one example, the ion conductivity of the halide solid electrolyte included in the first covering layer 111 is higher than the ion conductivity of the base material included in the second covering layer 112. According to this configuration, oxidation of other solid electrolytes can be further suppressed without sacrificing ion conductivity.

[0142] The thickness of the first coating layer 111 is, for example, greater than 1 nm and less than 500 nm. The thickness of the second coating layer 112 is, for example, greater than 1 nm and less than 500 nm. If the thickness of the first coating layer 111 and the second coating layer 112 is appropriately adjusted, the contact between the active material 110 and other solid electrolytes can be sufficiently suppressed. The thickness of each layer can be determined by the method described above.

[0143] 《Method for producing coated active material 140》

[0144] The coated active material 140 can be produced by the following method.

[0145] First, the second covering layer 112 is formed on the surface of the active material 110. The method for forming the second covering layer 112 is not particularly limited. Examples of the method for forming the second covering layer 112 include a liquid phase covering method and a gas phase covering method.

[0146] For example, in the liquid phase coating method, a precursor solution of the base material is applied to the surface of the active material 110. In the case of forming the second coating layer 112 containing LiNbO3, the precursor solution can be a mixed solution (sol solution) of a solvent, a lithium alkoxide, and a niobium alkoxide. As lithium alkoxide, lithium ethoxide can be listed. As niobium alkoxide, niobium ethoxide can be listed. The solvent is, for example, an alcohol such as ethanol. The amount of lithium alkoxide and niobium alkoxide is adjusted according to the target composition of the second coating layer 112. Water can be added to the precursor solution as needed. The precursor solution can be acidic or alkaline.

[0147] The method of applying the precursor solution to the surface of the active material 110 is not particularly limited. For example, the precursor solution can be applied to the surface of the active material 110 using a tumble granulation coating device. According to the tumble granulation coating device, the precursor solution can be blown onto the active material 110 while the active material 110 is rolled and flowed, and the precursor solution can be applied to the surface of the active material 110. Thus, a precursor film is formed on the surface of the active material 110. Then, the active material 110 coated with the precursor film is heat-treated. The gelation of the precursor film is promoted by the heat treatment, and the second coating layer 112 is formed.

[0148] Examples of the vapor phase coating method include pulsed laser deposition (PLD), vacuum evaporation, sputtering, thermal chemical vapor deposition (CVD), plasma chemical vapor deposition, etc. For example, in the PLD method, a high-energy pulse laser (e.g., KrF excimer, wavelength: 248 nm) is irradiated on an ion conductive material as a target, and the sublimated ion conductive material is deposited on the surface of the active material 110. When forming the second coating layer 112 of LiNbO3, LiNbO3 sintered to a high density is used as a target.

[0149] However, the method for forming the second covering layer 112 is not limited to the above method, and the second covering layer 112 can be formed by various methods such as spraying, spray dry coating, electrodeposition, dipping, and mechanical mixing using a disperser.

[0150] After the second covering layer 112 is formed, the first covering layer 111 is formed by the method described in Embodiment 1. In this way, the covered active material 140 can be obtained.

[0151] (Implementation Method 2)

[0152] Figure 3 This is a cross-sectional view showing a schematic structure of an electrode material 1000 according to the second embodiment.

[0153] The electrode material 1000 includes the coated active material 130 of the first embodiment and the second solid electrolyte 100. The electrode material 1000 may be a positive electrode material. The coated active material 140 of the modified example may be used instead of the coated active material 130, or the coated active material 140 of the modified example may be used together with the coated active material 130. The electrode material 1000 of this embodiment is suitable for reducing the increase in battery resistance caused by the endurance test.

[0154] The active material 110 covering the active material 130 is separated from the second solid electrolyte 100 by the coating layer 111. The active material 110 does not need to be in direct contact with the second solid electrolyte 100. This is because the coating layer 111 has ion conductivity.

[0155] The second solid electrolyte 100 may include at least one selected from the group consisting of a halide solid electrolyte, a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, and a complex hydride solid electrolyte.

[0156] Examples of the halide solid electrolyte include the materials described as the first solid electrolyte in Embodiment 1. That is, the composition of the second solid electrolyte 100 may be the same as or different from that of the first solid electrolyte.

[0157] The oxide solid electrolyte is a solid electrolyte containing oxygen. The oxide solid electrolyte may further contain anions other than sulfur and halogen elements as anions other than oxygen.

[0158] As oxide solid electrolytes, for example, NASICON solid electrolytes represented by LiTi2(PO4)3 and its element substitution products, (LaLi)TiO3-based perovskite solid electrolytes, and Li 14 ZnGe4O 16 , Li4SiO4, LiGeO4 and their element substitution bodies are represented by LISICON type solid electrolytes, such as Li7La3Zr2O 12 Garnet-type solid electrolytes represented by Li3PO4 and its element substitution bodies, Li3PO4 and its N substitution bodies, glass or glass ceramics with Li2SO4, Li2CO3 and other materials added to the basic materials containing Li-BO compounds such as LiBO2 and Li3BO3.

[0159] As a polymer solid electrolyte, for example, a compound of a polymer compound and a lithium salt can be used. The polymer compound can have an ethylene oxide structure. The polymer compound having an ethylene oxide structure can contain a large amount of lithium salt. Therefore, the ion conductivity can be further improved. As lithium salts, LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, etc. can be listed. One lithium salt selected from them can be used alone, or a mixture of two lithium salts selected from them can be used.

[0160] As the complex hydride solid electrolyte, for example, LiBH4-LiI, LiBH4-P2S5, etc. can be used.

[0161] The second solid electrolyte 100 may contain Li and S. In other words, the second solid electrolyte 100 may contain a sulfide solid electrolyte. The sulfide solid electrolyte has high ion conductivity and can improve the charge and discharge efficiency of the battery. On the other hand, the sulfide solid electrolyte sometimes has poor oxidation resistance. In the case where the battery contains a sulfide solid electrolyte as the second solid electrolyte 100, a high effect can be obtained by applying the technology disclosed in the present invention.

[0162] As sulfide solid electrolytes, for example, Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12 etc. LiX, Li2O, MO can be added to them q , Li p MO q Here, X in "LiX" is at least one selected from the group consisting of F, Cl, Br and I. q ” and “Li p MO q The element M in "MO" is at least one selected from the group consisting of P, Si, Ge, B, Al, Ga, In, Fe and Zn. q ” and “Li p MO q " where p and q are independent natural numbers.

[0163] The second solid electrolyte 100 may include two or more materials selected from the materials listed as the solid electrolyte. For example, the second solid electrolyte 100 may include a halide solid electrolyte and a sulfide solid electrolyte.

[0164] The second solid electrolyte 100 may have a higher lithium ion conductivity than the first solid electrolyte.

[0165] The second solid electrolyte 100 may contain inevitable impurities such as starting materials, by-products, and decomposition products used when synthesizing the solid electrolyte. The same applies to the first solid electrolyte.

[0166] The shape of the second solid electrolyte 100 is not particularly limited, and may be a needle shape, a sphere shape, an ellipsoidal sphere shape, etc. The shape of the second solid electrolyte 100 may be a particle shape.

[0167] When the second solid electrolyte 100 is in a granular shape (e.g., spherical), the median particle size may be 100 μm or less. When the median particle size is 100 μm or less, the coated active material 130 and the second solid electrolyte 100 may form a good dispersion state in the electrode material 1000. Therefore, the charge and discharge characteristics of the battery are improved. The median particle size of the second solid electrolyte 100 may be 10 μm or less.

[0168] The median particle size of the second solid electrolyte 100 may be smaller than the median particle size of the coated active material 130. With this configuration, the second solid electrolyte 100 and the coated active material 130 can be dispersed in a better state in the electrode material 1000.

[0169] The median particle size of the coated active material 130 may be greater than 0.1 μm and less than 100 μm. When the median particle size of the coated active material 130 is greater than 0.1 μm, the coated active material 130 and the second solid electrolyte 100 may form a good dispersion state in the electrode material 1000. As a result, the charge and discharge characteristics of the battery are improved. When the median particle size of the coated active material 130 is less than 100 μm, the diffusion rate of lithium inside the coated active material 130 may be sufficiently ensured. Therefore, the battery can operate at a high output power.

[0170] The median particle size of the coated active material 130 may be larger than the median particle size of the second solid electrolyte 100. Thus, the coated active material 130 and the second solid electrolyte 100 can be in a well-dispersed state.

[0171] In the electrode material 1000, the second solid electrolyte 100 and the coated active material 130 are as follows. Figure 3 At this time, the coating layer 111 and the second solid electrolyte 100 are in contact with each other.

[0172] The electrode material 1000 may include a plurality of particles of the second solid electrolyte 100 and a plurality of particles of the coated active material 130. That is, the electrode material 1000 may be a mixture of the powder of the coated active material 130 and the powder of the second solid electrolyte 100.

[0173] In the electrode material 1000 , the content of the second solid electrolyte 100 and the content of the coated active material 130 may be the same or different.

[0174] 《Other Materials》

[0175] In the electrode material 1000, for the purpose of improving the adhesion between particles, a binder can be included. The binder is used to improve the adhesion of the material constituting the electrode. As a binder, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polycarbonate, polyether sulfone, polyether ketone, polyether ether ketone, polyphenylene sulfide, hexafluoropolypropylene, styrene-butadiene rubber, carboxymethyl cellulose, ethyl cellulose, etc. can be listed. In addition, copolymers of more than two monomers selected from the group consisting of tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, trifluorochloroethylene, ethylene, propylene, butadiene, styrene, pentafluoropropylene, fluoromethyl vinyl ether, acrylate, acrylic acid and hexadiene can also be used. One selected from these may be used alone or two or more may be used in combination.

[0176] Based on the reason of excellent adhesiveness, the binder can be an elastomer. An elastomer is a polymer with rubber elasticity. The elastomer used as a binder can be a thermoplastic elastomer or a thermosetting elastomer. The binder can include a thermoplastic elastomer. As a thermoplastic elastomer, styrene-ethylene-butylene-styrene (SEBS), styrene-ethylene-propylene-styrene (SEPS), styrene-ethylene-ethylene-propylene-styrene (SEEPS), butadiene rubber (BR), isoprene rubber (IR), chloroprene rubber (CR), nitrile rubber (NBR), styrene-butadiene rubber (SBR), styrene-butadiene-styrene (SBS), styrene-isoprene-styrene (SIS), hydrogenated isoprene rubber (HIR), hydrogenated butyl rubber (HIIR), hydrogenated nitrile rubber (HNBR), hydrogenated styrene-butadiene rubber (HSBR), polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), etc. can be listed. One selected from them can be used alone, or two or more can be used in combination.

[0177] The electrode material 1000 may include a conductive additive for the purpose of improving electronic conductivity. As the conductive additive, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black and Ketjen black, conductive fibers such as carbon fibers or metal fibers, carbon fluoride, metal powders such as aluminum, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, conductive polymer compounds such as polyaniline, polypyrrole, and polythiophene, etc. can be used. When a carbon conductive additive is used, low cost can be achieved.

[0178] The conductive auxiliary agent may be contained in the coating layer 111 .

[0179] 《Method for producing electrode material》

[0180] The electrode material 1000 is obtained by mixing the powder of the coated active material 130 with the powder of the second solid electrolyte 100. There is no particular limitation on the method of mixing the coated active material 130 with the second solid electrolyte 100. The coated active material 130 and the second solid electrolyte 100 may be mixed using a mortar or other tool, or may be mixed using a mixing device such as a ball mill.

[0181] (Implementation 3)

[0182] Embodiment 3 will be described below. The description overlapping with Embodiment 1 and Embodiment 2 will be omitted as appropriate.

[0183] Figure 4 2 is a cross-sectional view showing a schematic structure of a battery 2000 according to Embodiment 3. The battery 2000 includes a positive electrode 201, a separator layer 202, and a negative electrode 203. The separator layer 202 is disposed between the positive electrode 201 and the negative electrode 203. The positive electrode 201 includes the electrode material 1000 described in Embodiment 2. According to this structure, an increase in resistance of the battery 2000 due to a durability test can be suppressed, and a battery with excellent durability can be provided.

[0184] The thickness of each of the positive electrode 201 and the negative electrode 203 can be 10 μm or more and 500 μm or less. When the thickness of the positive electrode 201 and the negative electrode 203 is 10 μm or more, sufficient energy density of the battery can be ensured. When the thickness of the positive electrode 201 and the negative electrode 203 is 500 μm or less, the battery 2000 can operate at high output power.

[0185] The separator layer 202 is an electrolyte layer containing an electrolyte material. The separator layer 202 may contain at least one solid electrolyte selected from the group consisting of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, a polymer solid electrolyte, and a complex hydride solid electrolyte. The details of each solid electrolyte are as described in Embodiments 1 and 2.

[0186] The thickness of the separator layer 202 may be greater than 1 μm and less than 300 μm. When the thickness of the separator layer 202 is greater than 1 μm, the positive electrode 201 and the negative electrode 203 can be more reliably separated. When the thickness of the separator layer 202 is less than 300 μm, the battery 2000 can operate at a high output power.

[0187] The negative electrode 203 includes a material having a property of storing and releasing metal ions (for example, lithium ions) as a negative electrode active material.

[0188] As the negative electrode active material, metal materials, carbon materials, oxides, nitrides, tin compounds, silicon compounds, etc. can be used. The metal material can be a single metal. Alternatively, the metal material can also be an alloy. As metal materials, lithium metal, lithium alloys, etc. can be listed. As carbon materials, natural graphite, coke, graphitized carbon, carbon fiber, spherical carbon, artificial graphite, amorphous carbon, etc. can be listed. From the perspective of capacity density, silicon (Si), tin (Sn), silicon compounds, tin compounds, etc. can be appropriately used.

[0189] The median particle size of the particles of the negative electrode active material may be 0.1 μm or more and 100 μm or less.

[0190] The negative electrode 203 may include other materials such as a solid electrolyte. As the solid electrolyte, the materials described in Embodiment 1 or 2 can be used.

[0191] Example

[0192] Hereinafter, the present disclosure will be described in detail using examples and comparative examples. It should be noted that the present disclosure is not limited to the following examples.

[0193] <Example 1>

[0194] [Production of halide solid electrolyte]

[0195] In an argon atmosphere with a dew point below -60°C, weigh LiF, TiF4 and AlF3 as raw material powders at a molar ratio of LiF:TiF4:AlF3=2.7:0.3:0.7. Put them together with a 0.5 mmφ ball (25 g) into a 45cc pot for a planetary ball mill. Add γ-butyrolactone (GBL) as an organic solvent dropwise into the pot in such a way that the solid content ratio reaches 50% by mass. The solid content ratio is calculated by {(mass of raw material) / (mass of raw material + mass of solvent)}×100. Grind the mixture using a planetary ball mill at 500 rpm for 12 hours. After grinding, separate the balls to obtain a slurry. Use an electric heating mantle to dry the slurry at 200°C for 1 hour under a nitrogen flow. Crush the obtained solid material with a mortar to obtain a powder of a halide solid electrolyte. The halide solid electrolyte has a composition composed of Li 2.7 Ti 0.3 Al 0.7 The composition represented by F6 (hereinafter referred to as "LTAF") In the SEM image, the diameter of each particle of the halide solid electrolyte is in the range of 10 nm to 100 nm.

[0196] [Preparation of coated active material]

[0197] As a positive electrode active material, powder of Li(NiCoAl)O2 (hereinafter referred to as "NCA") is prepared. Next, a coating layer formed of LTAF is formed on the surface of NCA. The coating layer is formed by a stirring treatment using a large-scale high-speed mixer (BG-25L manufactured by FREUND-TURBOCorporation). Specifically, NCA and LTAF are weighed in such a manner as to form a mass ratio of NCA:LTAF=97.3:2.7. Using a high-speed mixer, NCA and LTAF are stirred and mixed at 700 rpm for 1 hour. Then, NCA and LTAF are further stirred and mixed at 1300 rpm for 1 hour and at 1900 rpm for 0.17 hours (10 minutes). Thus, the coated active material of Example 1 is obtained.

[0198] In Table 1, for example, the expressions "rotation speed 700 rpm, 1300 rpm" and "treatment time 1+1" mean that the treatment is performed at a rotation speed of 1700 rpm for 1 hour and then at a rotation speed of 1300 rpm for 1 hour.

[0199] [XPS measurement of coated active material]

[0200] The XPS measurement of the coated active material of Example 1 was performed under the following conditions. Quantera SXM (manufactured by ULVAC-PHI, Inc.) was used for the XPS measurement. The measurement conditions are as follows.

[0201] X-ray source: Al monochromatic source (25W, 15kV)

[0202] Electron / ion neutralization gun: ON

[0203] Photoelectron emission angle: 45 degrees

[0204] Ti was selected as the element to be measured, and the scanning range of the bonding energy was set to 450eV~470eV (Ti2p orbital). The peaks of the XPS spectrum in the range of 455eV~486eV were separated, and the area of ​​each peak was calculated. In detail, the spectrum was separated into peaks belonging to the Ti-F bond, peaks belonging to the Ti-OF bond, and peaks belonging to the Ti-O bond, and the area of ​​each peak (integrated peak area) was calculated. The ratio of the sum of the area of ​​the peak belonging to the Ti-O bond and the area of ​​the peak belonging to the Ti-OF bond to the total area of ​​the peak was calculated (unit: %). This ratio is the ratio of the sum of Ti-OF bonds and Ti-O bonds in the bond group of Ti. The XPS spectrum was analyzed by peak fitting using the Gaussian-Lorentzian function. The peak position of each bond cannot be determined uniformly due to the influence of charge, so the relative positions and intensity ratios of the multiple peaks of each component are fixed for fitting. The results are shown in Tables 1 and Figure 5A .

[0205] [Production of sulfide solid electrolyte]

[0206] In an argon glove box with a dew point below -60°C, Li2S and P2S5 are weighed in a molar ratio of Li2S:P2S5=75:25. They are crushed and mixed in a mortar to obtain a mixture. Then, the mixture is ground using a planetary ball mill (P-7 model manufactured by Fritsch) at 510 rpm for 10 hours. Thus, a glassy solid electrolyte is obtained. The glassy solid electrolyte is heat treated in an inactive atmosphere at 270°C for 2 hours. Thus, a glass-ceramic-like Li2S-P2S5 as a sulfide solid electrolyte is obtained.

[0207] [Battery production]

[0208] (Production of positive electrode)

[0209] The coated active material and the sulfide solid electrolyte of Example 1 are weighed in such a manner as to form a volume ratio of (coated active material): (sulfide solid electrolyte) = 6:4. They are added to a tetrahydroxynaphthalene solvent together with vapor-grown carbon fiber (VGCF) as a conductive aid and styrene-ethylene-butylene-styrene block copolymer (SEBS) as a binder. The resulting mixture is fully dispersed using an ultrasonic homogenizer to prepare a positive electrode paste. The amount of the conductive aid is 3 parts by mass relative to 100 parts by mass of the coated active material. The amount of the binder is 0.4 parts by mass relative to 100 parts by mass of the coated active material. "VGCF" is a registered trademark of Lisennoco Corporation.

[0210] (Production of negative electrode)

[0211] Lithium titanate and sulfide solid electrolyte as negative electrode active materials are weighed in a volume ratio of (lithium titanate): (sulfide solid electrolyte) = 6.5:3.5. They are added to a tetralin solvent together with vapor-grown carbon fiber (VGCF) as a conductive aid and styrene-ethylene-butylene-styrene block copolymer (SEBS) as a binder. The resulting mixture is fully dispersed using an ultrasonic homogenizer to prepare a negative electrode paste. The amount of the conductive aid is 1 part by mass relative to 100 parts by mass of the negative electrode active material. The amount of the binder is 2 parts by mass relative to 100 parts by mass of the negative electrode active material.

[0212] (Production of all-solid-state batteries)

[0213] The positive electrode paste was applied to an aluminum foil as a positive electrode current collector by a doctor blade method using a coating device to form a coating film. The coating film was dried on a hot plate at 100° C. for 30 minutes. Thus, a positive electrode having a positive electrode current collector and a positive electrode active material layer was obtained.

[0214] Next, the positive electrode is pressed. The electrolyte layer forming paste is applied to the surface of the pressed positive electrode active material layer using a die coater to obtain a stack of the positive electrode and the coating film. The stack is dried on a hot plate at 100°C for 30 minutes. Then, the stack is rolled at a linear pressure of 2 ton / cm. Thus, a positive electrode side stack having a positive electrode collector, a positive electrode active material layer and a solid electrolyte layer is obtained. The electrolyte layer forming paste is prepared by dispersing 0.4 parts by mass of acrylate butadiene rubber as a binder and 100 parts by mass of a sulfide solid electrolyte in a heptane solvent using ultrasound.

[0215] The negative electrode paste was applied on a nickel foil as a negative electrode current collector to form a coating film, and the coating film was dried on a hot plate at 100° C. for 30 minutes. Thus, a negative electrode having a negative electrode current collector and a negative electrode active material layer was obtained.

[0216] Next, the negative electrode is pressed. The paste for forming the electrolyte layer is applied to the surface of the pressed negative electrode active material layer using a die coater to obtain a laminate of the negative electrode and the coating film. The laminate is dried on a hot plate at 100°C for 30 minutes. Then, the laminate is rolled at a linear pressure of 2 ton / cm. Thus, a negative electrode side laminate having a negative electrode collector, a negative electrode active material layer and a solid electrolyte layer is obtained.

[0217] The positive electrode side laminate and the negative electrode side laminate are punched and processed separately to prepare a specified shape. The positive electrode side laminate and the negative electrode side laminate are stacked in a manner that the solid electrolyte layers are in contact with each other. Then, the positive electrode side laminate and the negative electrode side laminate are rolled at 130°C and a line pressure of 2 ton / cm. Thus, a power generation element having a positive electrode, a solid electrolyte layer and a negative electrode in sequence is obtained. The positive terminal and the negative terminal are installed on the obtained power generation element, and a container made of a laminated film is sealed and constrained at a pressure of 5 MPa, thereby obtaining the all-solid-state battery of Example 1.

[0218] [DC resistance measurement]

[0219] The DC resistance of the all-solid-state battery was measured as follows. Constant current charging was performed at a current of 1C. After the cell voltage reached 2.95V, constant voltage charging was performed at 2.95V, and charging was terminated when the charging current reached 0.01C. Then, constant current discharge was performed at a current of 1C, and discharge was terminated when the cell voltage dropped to 1.5V.

[0220] In order to measure the DC resistance, the all-solid-state battery was charged again to 2.2V at a current of C / 3, and then discharged at a current of 4C. The DC resistance (initial resistance) was calculated by dividing the difference between the open circuit voltage just before the 4C discharge and the voltage at the moment when 10 seconds had passed from the start of the discharge by the current value of 4C. The results are shown in Table 1.

[0221] [Durability test]

[0222] The all-solid-state battery was placed in a 60°C thermostat and charged and discharged for 90 cycles at a current of 1C. Then, the all-solid-state battery was returned to the 25°C thermostat and the DC resistance was measured according to the method described above to calculate the DC resistance after the endurance test. The ratio of the DC resistance after the endurance test to the DC resistance before the endurance test was calculated as the resistance increase factor.

[0223] <Example 2>

[0224] The coated active material of Example 2 was prepared in the same manner as in Example 1, except that the treatment using the high-speed mixer was performed at 700 rpm for 1 hour, at 1300 rpm for 1 hour, and at 1900 rpm for 0.5 hour (30 minutes). Then, the XPS measurement of the coated active material of Example 2 was performed in the same manner as in Example 1. Using the coated active material of Example 2, an all-solid-state battery was prepared in the same manner as in Example 1, and the resistance increase rate was measured.

[0225] <Example 3>

[0226] The coated active material of Example 3 was prepared in the same manner as in Example 1 except that the treatment using the high-speed mixer was performed at 700 rpm for 1 hour, at 1300 rpm for 1 hour, and at 1900 rpm for 1 hour. Then, the XPS measurement of the coated active material of Example 3 was performed in the same manner as in Example 1. Using the coated active material of Example 3, an all-solid-state battery was prepared in the same manner as in Example 1, and the resistance increase rate was measured.

[0227] <Example 4>

[0228] [Preparation of coated active material]

[0229] As a positive electrode active material, NCA powder is prepared. Next, a coating layer is formed on the surface of NCA using LTAF having a particle diameter of 10 nm to 100 nm. The coating layer is formed by stirring treatment using a small high-speed mixer (BG-2L manufactured by FREUND-TURBOCorporation). Specifically, NCA and LTAF are weighed in such a manner as to form a mass ratio of NCA:LTAF=97.3:2.7. Using a small high-speed mixer, they are stirred and mixed at 2300 rpm for 1 hour. Then, the rotation speed is changed to 3580 rpm, and stirring and mixing are performed for 1.5 hours. Thus, the coated active material of Example 4 is obtained.

[0230] Then, XPS measurement of the coated active material of Example 4 was performed in the same manner as in Example 1. Using the coated active material of Example 4, an all-solid-state battery was produced in the same manner as in Example 1, and the resistance increase factor was measured.

[0231] <Comparative Example 1>

[0232] The coated active material of Comparative Example 1 was prepared in the same manner as in Example 1 except that the treatment was carried out using a high-speed mixer at 700 rpm for 1 hour and then at 1300 rpm for 1 hour. Then, the XPS measurement of the coated active material of Comparative Example 1 was carried out in the same manner as in Example 1. Using the coated active material of Comparative Example 1, an all-solid-state battery was prepared in the same manner as in Example 1, and the increase rate of resistance was measured. The Ti2p XPS spectrum of Comparative Example 1 is shown in Figure 5B .

[0233] The calculation results of the resistance increase factor and the results of XPS measurement are shown in Table 1. In Table 1, the resistance increase factor is a relative value when the resistance increase factor of Comparative Example 1 is regarded as "100".

[0234] Figure 6 : This is a graph showing the relationship between the ratio of Ti-O bonds to Ti-OF bonds and the increase rate of resistance. The horizontal axis shows the ratio of the total of Ti-O bonds and Ti-OF bonds in the bond group to Ti in Table 1. The vertical axis shows the increase rate of resistance in Table 1.

[0235] [Table 1]

[0236]

[0237] ※The increase ratio of resistance is a relative value when the value of Comparative Example 1 is regarded as 100.

[0238] <Inspection>

[0239] As shown in Table 1 and Figure 6 As shown, as the total ratio of Ti-O bonds and Ti-OF bonds increases, the increase rate of resistance decreases. The total ratio of Ti-O bonds and Ti-OF bonds increases as the rotation speed of the mixing device increases, and increases as the processing time increases. It can be considered that by fully pressing the particles of LTAF onto the particles of NCA, the particles of LTAF are fully attached to the active material. It can be considered that, due to the good bonding between the coating layer and the active material, it is not easy to produce peeling at the interface between materials (such as the coated active material and the sulfide granular solid electrolyte) during repeated charge and discharge, and as a result, the increase in resistance can be suppressed.

[0240] It is inferred from the above mechanism that the desired effect can be obtained even when a solid electrolyte other than LTAF is used as long as a solid electrolyte containing Ti and F is used. It is also inferred that the desired effect can be obtained when the active material is other than NCA.

[0241] Industrial Applicability

[0242] The technology disclosed herein is useful for, for example, all-solid-state lithium secondary batteries.

Claims

1. A coated active material, comprising: an active material, and a coating layer that contains a first solid electrolyte and coats at least a part of the surface of the active material, wherein the first solid electrolyte contains a Ti-containing fluoride, and the ratio of the total of Ti-O-F bonds and Ti-O bonds in the bond groups of Ti contained in the first solid electrolyte is greater than 70%.

2. The coated active material according to claim 1, wherein the ratio is 92% or less.

3. The coated active material according to claim 1, wherein the coating layer has a granular structure including a plurality of particles with a diameter of 500 nm or less.

4. The coated active material according to claim 1, wherein the coating layer has a plurality of pores with a diameter of 50 nm or less.

5. The coated active material according to claim 1, wherein the mass of the coating layer is 4.5% or less of the mass of the coated active material.

6. The coated active material according to claim 1, wherein the active material is a positive electrode active material.

7. The coated active material according to claim 1, wherein the first solid electrolyte is represented by the following compositional formula (2): Li 6-nx M x X6… Formula (2) Here, x satisfies 0 < x ≤ 1.2, n is the weighted average valence of the elements contained in M, M is a metal or a semi-metal and contains at least Ti, and X contains fluorine or contains fluorine and chlorine.

8. The coated active material according to claim 7, wherein M is at least one selected from the group consisting of Ca, Mg, Al, Y, Ti, and Zr and contains Ti.

9. The coated active material according to claim 7, wherein M is at least one selected from the group consisting of Al, Ti, and Zr and contains Ti.

10. The coated active material according to claim 7, wherein M is Ti or Ti and Al.

11. The coated active material according to claim 7, wherein the ratio of the amount of substance of Li to the total amount of substance of M is 1.7 or more and 4.2 or less.

12. An electrode material, comprising: the coated active material according to claim 1, and a second solid electrolyte.

13. The electrode material according to claim 12, wherein the second solid electrolyte contains a sulfide solid electrolyte.

14. A battery comprising a positive electrode containing the electrode material according to claim 12.

15. A battery, comprising: a positive electrode containing the electrode material according to claim 12, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode.